IMPLEMENTATION OF SUSTAINABILITY CONCEPT ON RETAIL INDUSTRY - Willy Arafah (Business and Entrepreneurial Review, 2014)
The objectives of this paper seek to know how sustainability concept and implementation of the retail industry in Indonesia based on sustainability theoretical framework. The research was conducted in Jakarta (Indonesia), the survey was carried out on the basis of questionnaire that was used as a support during the interviews. A total of 137 Indonesia retail enterprises were involved in the research. The results achieved highlight, how CSR does make business sense in Indonesia context. This process calls for new forms of collaboration involving firms along the supply chain, local authorities, the international player and civil society. The conclusion of this research how CSR become a mandatory requirement for access to the International market, transform itself into a new type of technical barrier to trade. CSR need to be fostered rather than imposed through the creation of innovative partnership and locally rooted solution